(3efThQ Edi GdeMd GdCRgQ GdTQjas - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdZahQ GdHGQ Edg GdYGdejf hJhSdJ Edjg Hhdjg GdeJbe ef CYOGA GdOjf ef GdYHO Gdeedhc dhdi GdReGf hGdOghQ s
(3BNQgG (B:s
(3hCfG CSJhOY LeGYI ENhGfi def GdhOGFY ai MaXg dGJHGM hgh MSHi hHg CSJYjf GdTcQ dhdjg GdgGOi YHOg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds